(a+b+c)的平方-3(ab+bc+ca)
=a^2+b^2+c^2-ab-bc-ca
=1/2*(a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ca+a^2)
1/2*((a-b)^2+(b-c)^2+(c-a)^2)
因为上式=0,所以:a=b=c
b^2-4ac=(ak+c/k)^2-4ac=(ak)^2-2ac-(c/k)^2
=(ak-c/k)^2>=0
所以两根也是有理数
(a+b+c)的平方-3(ab+bc+ca)
=a^2+b^2+c^2-ab-bc-ca
=1/2*(a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ca+a^2)
1/2*((a-b)^2+(b-c)^2+(c-a)^2)
因为上式=0,所以:a=b=c
b^2-4ac=(ak+c/k)^2-4ac=(ak)^2-2ac-(c/k)^2
=(ak-c/k)^2>=0
所以两根也是有理数
(a+b+c)的平方-3(ab+bc+ca)
=a^2+b^2+c^2-ab-bc-ca
=1/2*(a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ca+a^2)
1/2*((a-b)^2+(b-c)^2+(c-a)^2)
因为上式=0,所以:a=b=c
b^2-4ac=(ak+c/k)^2-4ac=(ak)^2-2ac-(c/k)^2
=(ak-c/k)^2>=0
所以两根也是有理数
(a+b+c)的平方-3(ab+bc+ca)
=a^2+b^2+c^2-ab-bc-ca
=1/2*(a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ca+a^2)
1/2*((a-b)^2+(b-c)^2+(c-a)^2)
因为上式=0,所以:a=b=c
b^2-4ac=(ak+c/k)^2-4ac=(ak)^2-2ac-(c/k)^2
=(ak-c/k)^2>=0
所以两根也是有理数